THE BORDER AS A RESOURCE FOR THE DEVELOPMENT OF BORDERLAND: A COMPARATIVE ANALYSIS OF TWO POLISH URBAN CENTRES AT THE EXTERNAL BORDER OF THE EUROPEAN UNION - Studzińska, Dominika; Domaniewski, Stanisław (Quaestiones Geographicae, 2016)
The entry into force of the Agreement between the Republic of Poland and the Russian Federation on visa-free movement in 2012 caused an increase in border permeability, and hence a sudden increase in border crossings. The border which used to divide the neighbouring states started linking them instead. Crossing the border became part of the everyday life of local communities. Actors on both sides benefited from the commercial services of the other country. For Kaliningrad citizens, border-crossing points became gates to Europe, and for Poles, a resource improving the quality of life via petty trade. The aim of this article is to compare two border cities: Braniewo, a town located in the immediate vicinity of the border-crossing point, and Tri City, which has become a new border centre after the introduction of small border traffic. Two viewpoints on the effect of local border traffic are presented. The first is the perspective of a typical border city. The other is that of the effect of an increase in border permeability on a major urban centre – Tri-City.